The sustainable competitive advantage: Elements of business strategy for surviving in the franchising industry / Shaira Ismail - Ismail, Shaira (Universiti Teknologi MARA, Pulau Pinang & and Pusat Penerbitan Universiti (UPENA), 2009)
Competitive position is a firm's position relative to its competition in the market. Firms should identify its strengths to build on and weaknesses to overcome when formulating strategies for competitive advantage. Firms should seek out the best example or practice in the industry to improve and assess where they stand on overall performance and benchmark their position in the industry. The aim of this research is to identify the factors and business strategies contributing to the firms' competitive advantage in order to secure and sustain itself in the franchise business. A set of questionnaire was developed and distributed to the selected franchisees. The survey results showed that the extremely important factors contributing to a company's competitive advantage are related to customers and products aspects. A business sustainable competitive advantage (SCA) is a combination of elements of the business strategies such as satisfying customers needs, franchisor and franchisee relationships, capitalizing on organizational resources, business location, marketing and promotional activities, product management, maintaining high quality of products and services, business management system and so forth. On the other hand, skills, business know how, self-confidence and capability would also give an implication to the entrepreneurs' decision making. A look at the discussion above indicates mainly on the business sustainable factors and competitive advantage.